Механіко-технологічні основи глибокої переробки насіння рицини в умовах малотоннажного підприємства - Дідур, Володимир Володимирович; Didur, Volodymir (Мелітополь : 2021, 2021)
UA: При дослідженні технологічних процесів переробки насіння рицини за основу були взяті три основних процеси, а саме: процес волого-теплової обробки м’ятки; процес віджиму олії із мезги в гвинтових пресах та процес очищення віджатої олії. Особливостю процесу віджиму рослинних олій в гвинтовому пресі є безперервне зменшення пористості матеріалу. Підвищення якісних показників рицинової олії і зниження її втрат у макусі кінцевого пресування досягалося шляхом раціональної волого-теплової обробки. Це забезпечує зниження зв’язку олії з гелевою частиною і підготовки раціонального поєднання пластичності і пружності структури і наступних режимів консолідації мезги при проходженні через витки гвинтового преса в зеєрній камері. Процес очищення пресової олії від механічних домішок і фосфоліпідів нами представлений як процес електрофлотації попередньо гідратованої олії. Робочі гіпотези наведених процесів полягали в наступному: водяні бульбашки води, що присутні в об’ємі олії під дією електричного поля починають рухатися в міжелектродному просторі при цьому їх температура зростає. Крапля води перетворюється в газову бульбашку і переміщується на поверхню, адсорбуючи на себе фосфоліпіди та механічні домішки. Висунуті гіпотези підтверджувались шляхом числових досліджень математичних моделей та експериментальних досліджень закономірностей впливу технологічних режимів і конструкційних параметрів обладнання на вихід олії та її якість. Підтвердження висунутих гіпотез перевірялись експериментальним шляхом за допомогою спеціально спроектованого та виготовленогообладнання. Таким чином, в результаті виконання теоретичних і експериментальних досліджень отримані вихідні вимоги і розроблено «Технологічний регламент» для проектування технологічної лінії, і окремого обладнання для переробки рицини в умовах малотоннажного підприємства. Підприємства продуктивністю 30 т/добу по початковій сировині в рік перероблятимуть 9000 т насіння рицини і будуть випускати 4624 т технічної рицинової олії, 2626 т рицинової кормової високопротеїнової макухи і 700 т лушпиння, яке використовуватиметься як сухе біопаливо для виробництва технологічної пари високого тиску. Чистий річний прибуток такого заводу складе близько 22,6 млн.грн. EN: During the study of technological processes of castor seed processing, three main processes were taken as a basis, namely: the process of wet-heat treatment of gritted seeds; the process of oil extraction from the pulp in screw presses and the process of cleaning of pressed oil. Among the factors that previously were not taken into account when studying the process of wet-heat treatment of gritted seeds, the most significant are: the energy of binding the moisture to the skeleton of gritted seeds and the influence of hydrodynamics of the movement of gritted seeds in the roaster under the influence of a vane turbine located at the bottom of each vat. Distinctive features of the process of pressing vegetable oils in a screw press, which distinguishes it from the phenomena that are considered in the classical theories of filtration and migration, is a continuous decrease in the porosity of the material. When studying the process of extracting oil by pressing in screw presses, the following hypothesis is accepted: the process of extracting oil in screw presses can be described by general processes of movement of the pulp, like the movement of polymer in the channels of worm machines, the movement of oil using the theory of filtering currents in soils taking into account special features of the pulp, oil and conditions in the pressing cage chamber of the screw press. The process of cleaning press oil from mechanical particles and phospholipids is presented as the process of electroflotation of prematurely hydrated oil. The working hypotheses of the above processes are as follows: the water bubbles which are present in the volume of oil under the action of an electric field begin to move in between the electrical space while their temperature increases. In this case, a drop of water turns into a gas bubble and moves to the surface, adsorbing phospholipids and mechanical impurities on it. These hypotheses were confirmed by numerous studies of mathematical models and experimental studies of the patterns of influence of technological regimes and design parameters of equipment on the oil yield and its quality. Confirmation of the hypotheses put forward was tested experimentally with the help of specially designed and manufactured equipment. For experimental studies of the process of cleaning the pressed oil, a laboratory complex including a hydrator and an electric flotation unit has been developed. With the help of this complex, the adequacy of the mathematical model of the dynamics of the movement of vapor-air particles under the action of an electric field was tested and a method was developed for calculating the technological regimes and design parameters of the installation for cleaning pressed oil. Thus, as a result of the implementation of theoretical and experimental studies, initial requirements have been obtained and a “Technological regulation” has been developed for the design of a technological line, and separate equipment for castor processing in the light-tonnage enterprise. Enterprises with the capacity of 30 tons per day of feedstock per year will process 9000 tons of castor seeds and will produce 4624 tons of technical castor oil, 2626 tons of castor fodder high protein meal and 700 tons of husk, which will be used as dry nature-friendly fuel for the production of high-pressure process steam. The net annual profit of such an enterprise will be about 22.6 million UAH.
Mechanical and technological bases of deep processing of castor seeds in the conditions of small tonnage enterprise
Keywords: малотоннажне підприємство; м’ятка мезги; вологотеплова обробка; тепло-масоперенос; конвективний нагрів; кондуктивний нагрів; енергія зв’язку; консолідація; фільтрація; електрофлотація; тепловий баланс; матеріальний баланс; гвинтовий прес; експелерний прес; low-tonnage enterprise; gritted seeds; pulp; wet-heat treatment; heat and mass transfer; convective; conductive heating; binding energy; consolidation; filtration; electrical flotation; heat balance; material balance; screw press; expeller press